Neuropsychiatric presentation of Wilson’s disease - Dhungana, S; Ojha, SP; Chapagain, M; Tulachan, P; Pant, SB (Journal of Institute of Medicine Nepal, 2016)
Wilson’s disease is a rare autosomal inherited disorder with various manifestations. Initial manifestations could be hepatic, neurological or psychiatric and there is invariable delay coming to the correct diagnosis. Exact frequency of children and adolescents presenting with psychiatric complaint as the initial manifestation is not known. It is recommended that detailed medical evaluation be done in any child presenting with psychiatric complaints. We hereby present a case of an eight-year old girl who presented with anxiety and subsequently diagnosed to have Wilson’s disease.